2023
DOI: 10.1007/s00432-023-04602-8
|View full text |Cite
|
Sign up to set email alerts
|

Common inherited variants of PDCD1, CD274 and HAVCR2 genes differentially modulate the risk and prognosis of adenocarcinoma and squamous cell carcinoma

Abstract: Background To investigate the association between single nucleotide polymorphisms (SNPs) of PDCD1, CD274, and HAVCR2 genes with the risk and outcomes of non-small cell lung cancer (NSCLC) subtypes: squamous cell lung cancer (LUSC) and lung adenocarcinoma (LUAD). Methods TaqMan SNP genotyping assays or polymerase chain reaction-restriction fragment length polymorphism methods were used to determine genotypes of: PDCD1: rs36084323, rs7421861, rs11568821, rs2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…35 In a Polish study of non-small cell lung cancer, a higher frequency of CC genotype at the rs4143815 locus in the patient group than in healthy controls was noted (OR = 2.31). 36 For patients with chronic lymphatic filariasis, rs4143815 showed no difference in genotype distribution between patients and healthy controls in the south Indian population. 37 In the present study, the frequencies of CC genotype and C allele at the rs4143815 locus were found to be significantly lower in SLE patients than in healthy controls, suggesting that the rs4143815 polymorphism is associated with lower risk of SLE in the Chinese Han population and may be a protective factor for SLE development.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…35 In a Polish study of non-small cell lung cancer, a higher frequency of CC genotype at the rs4143815 locus in the patient group than in healthy controls was noted (OR = 2.31). 36 For patients with chronic lymphatic filariasis, rs4143815 showed no difference in genotype distribution between patients and healthy controls in the south Indian population. 37 In the present study, the frequencies of CC genotype and C allele at the rs4143815 locus were found to be significantly lower in SLE patients than in healthy controls, suggesting that the rs4143815 polymorphism is associated with lower risk of SLE in the Chinese Han population and may be a protective factor for SLE development.…”
Section: Discussionmentioning
confidence: 93%
“…Genome‐wide association analysis showed that the rs4143815 locus is associated with type I diabetes (T1D) susceptibility and the patients carrying C allele had a lower risk of developing T1D 35 . In a Polish study of non‐small cell lung cancer, a higher frequency of CC genotype at the rs4143815 locus in the patient group than in healthy controls was noted (OR = 2.31) 36 . For patients with chronic lymphatic filariasis, rs4143815 showed no difference in genotype distribution between patients and healthy controls in the south Indian population 37 .…”
Section: Discussionmentioning
confidence: 99%
“…The polymorphism of this SNP was also associated with various diseases. For example, GG genotype was associated with poor prognosis in lung adenocarcinoma and squamous cell carcinoma ( 31 ), the CC genotype was associated with a two times higher risk of developing squamous cell lung cancer ( 32 ), G-allele was associated with poor outcomes in the early stage non-small cell lung cancer ( 33 ), the CC genotype has significantly reduced the risk of breast cancer ( 34 ), individuals carrying the C-allele of rs4143815 had less risk of type 1 diabetes ( 35 ), and so on. In addition, a functional study has already demonstrated that the rs4143815 C>G variant reduced transcriptional activity of the PDL1 gene ( 33 ), which indicated that the statistical association between rs4143815 and the diseases may be due to the gene expression level alteration caused by SNP variation, which in turn contributes to the development of the diseases.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study illustrated that CTLA4 blocked with ipilimumab (a blocking antibody of CTLA4) induces cancer regression in some metastatic RCC patients [ 30 ]. PDCD1 and CD274 differentially modulate the prognosis in lung adenocarcinoma or squamous cell carcinoma [ 31 ], and rational combinations of first series (CTLA-4, PD-1 and PD-L1) and second series (TIGIT, TIM-3 and LAG-3) of inhibitory receptors might be an optimal immunotherapy approach because of the coexpression or/and compensatory mechanisms in various cancers [ 32 ]. Therefore, exploring the specific functions and mechanisms of PRPCDGs in KIRC could provide a reference for targeted therapies.…”
Section: Discussionmentioning
confidence: 99%